2020
DOI: 10.1111/jocn.15186
|View full text |Cite
|
Sign up to set email alerts
|

Impact of self‐care programmes in type 2 diabetes mellitus population in primary health care: Systematic review and meta‐analysis

Abstract: Aims and Objectives: To evaluate the effectiveness of self-care programmes in type 2 diabetes mellitus (T2DM) population in primary health care. Background: The impact of educational interventions on T2DM has been evaluated in various contexts, but there is uncertainty about their impact in that of primary care. Design: Systematic review and meta-analysis. Methods: A search was conducted in PubMed, CINAHL, WOS and Cochrane databases for randomised controlled trials carried out in the period January 2005-Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 55 publications
2
20
0
1
Order By: Relevance
“…The chief drive for diabetes care is not only the availability and adequacy of the health care workforce but the level of knowledge and skills needed for caring for the subjects. This because not all health care workers know about diabetes care, rather it necessitates special trainings and mentoring by experienced health providers [13].…”
Section: Discussionmentioning
confidence: 99%
“…The chief drive for diabetes care is not only the availability and adequacy of the health care workforce but the level of knowledge and skills needed for caring for the subjects. This because not all health care workers know about diabetes care, rather it necessitates special trainings and mentoring by experienced health providers [13].…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we searched the PubMed, CINAHL, Web of Science, and Cochrane databases for relevant RCTs. The search strategy, the results obtained (with meta‐analysis), the degree of quality of the evidence (GRADE system), and the description of each intervention considered have been presented in a systematic review (Caro‐Bautista et al., 2020).…”
Section: The Studymentioning
confidence: 99%
“…This variability makes it very difficult for a given program to be replicable with the same characteristics in different populations. Furthermore, these studies show significant methodological weaknesses, present a high risk of bias and are subject to inconsistency and indirectness in the results obtained (Caro‐Bautista et al., 2020). These shortcomings greatly limit the scope for transferring experimental results to clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the total energy intake, rather than the macro-nutrient composition of diets, has the most impact on glycaemic control, weight loss and cardiovascular risk factors ( Neuenschwander et al , 2019 ; Pan et al , 2019 ; Schwingshackl et al , 2018 ). Nutritional therapy has impressive effects in controlled research settings, but in everyday-life things are more complex; previous T2DM interventions using diet only resulted in small declines in weight and glycaemic blood markers ( Caro-Bautista et al , 2020 ; Coster and Norman, 2009 ; Franz et al , 2015 ; Norris et al , 2005 ), and sustaining health effects appears to be even more difficult ( Coster and Norman, 2009 ; Franz et al , 2007 , 2015 ; Turk et al , 2009 ).…”
Section: Introductionmentioning
confidence: 99%